Acoustic Analysis of Prosodic Features in Natural versus Synthesized Speech Samples from YourTTS and SYNTACC Models - Galdino, Julio Cesar; Araújo, Gustavo Evangelista; Candido Junior, Arnaldo; Oliveira Jr., Miguel; Ponti, Moacir Antonelli; Aluísio, Sandra Maria (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2024: Anais do XXI Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2024.245092, 2024)
This study presents an acoustic analysis of prosodic features in both natural and synthesized speech samples, using two state-of-the-art speech synthesis models: YourTTS and SYNTACC. By analyzing spontaneous speech data, the duration of intonational units and syllables produced by these models was compared. The findings reveal that both models generate speech with significantly shorter and less variable durations of intonational units and syllables compared to natural speech. These results highlight the differences in syllable duration and speech rate between synthesized and natural speech, emphasizing the need for more refined prosodic metrics to accurately assess the quality of synthesized speech.